Relationship between performance in game actions and the match result. A study in volleyball training stages - Claver Rabaz, F.; Jiménez Castuera, R.; Gil-Arias, A.; Moreno Dominguez, A.; Moreno Arroyo, M. P. (Journal of Human Sport & Exercise, 2013)
In recent years, a number of quantitative methods have been identified and developed with the specific intent of assisting the objective analysis of athletic performance (Nelson & Groom, 2012). The main aim of this research was to clarify the importance of performance in game actions as determinant of match result in a sample of young volleyball male players. The study sample was composed of 74 male participants belonging to the Under-16 teams (M: 14.61; SD: .88) from the Extremadura Volleyball League in the 2010/2011 season. The studied variables were: performance in game actions (serve, defense, setting and spike) and match result (win/lost). FIVB Observational System (Coleman, 1975) has been the instrument for data recollection, it has been applied previously in numerous studies and is accepted as a valid tool for research community. The T-test for independent samples results showed statistically significant differences in performance of game actions: serve (F1,72= 3.86; p=.048; np2=.492), defense (F1,72=14.07; p<.001.; np2=.959), setting (F1,72=34.83; p<.001.; np2=1.00) and spike (F1,72=9.05 ; p=.004; np2=.84) between players from winner and loser teams. Our results coincide with previous studies that emphasize the importance of game actions in volleyball (Asterios et al., 2009). This analysis is important as it assists in the collection of performance information that can feedback athletes in an attempt to enhance their understanding and competitive performance (Maslovat & Franks, 2008) and also for talent identification and recruitment (Carling et al., 2005).